2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5625970
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time varying currents and magnetic fields in the frequency range of 1 kHz to 1 MHz to the human body - a simulation study

Abstract: Exposure to time-varying magnetic fields evokes two effects in biological tissue: Firstly, an electric field is induced that generates eddy currents in conductive tissues, and, secondly, power deposit might increase local temperatures. Field effects of frequencies up to 1 kHz and above 1 MHz are well known. The intermediate frequency range lacks intensive research. Only little attention has been paid so far. Yet due to recent innovations in medical diagnostics and therapies like Magnetic Particle Imaging or RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…8. Percent overestimation caused by the approximate FLM given in (11) when compared to the exact relation in (19), plotted for various values. For , the error caused by the simplified relation is 9.8% at 1 KHz, decreasing very rapidly to below 1% at 6 kHz.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8. Percent overestimation caused by the approximate FLM given in (11) when compared to the exact relation in (19), plotted for various values. For , the error caused by the simplified relation is 9.8% at 1 KHz, decreasing very rapidly to below 1% at 6 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…It can be shown that for the E-field to be larger than , the derivative of the magnetic field has to be greater than (14) The time points that do not satisfy this criterion should not be included while calculating the thresholds, as they will otherwise result in an overestimation of the limits. Hence, for , the time points that contribute to stimulation have to satisfy (15) For time points between (i.e., in one period of the pulse), this corresponds to (16) The B-field at time point can be calculated as (17) Using (9) and , the B-field excursion from time point to will result in a stimulation if (18) Combining (16) - (18), the exact relation for FLM can be written as (19) Any field greater than a peak-to-peak amplitude of will induce a PNS sensation in the subjects. Because there is no closed form solution for , it must be computed numerically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the signal-to-noise ratio for a 10-kHz drivefield frequency is decreased owing to the lower dM/dt compared with the 25-kHz MPI systems. The influence of drive-field frequency and its signal strength on the generation of action potentials in nerves is currently under discussion [2,20].…”
Section: Introductionmentioning
confidence: 99%